2009
DOI: 10.31399/asm.cp.itsc2009p0051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microstructure on Thermal Conductivity of Plasma-Sprayed YSZ Coating

Abstract: Thermal conductivity of plasma-sprayed YSZ thermal barrier coatings depends on microstructure and significantly influences the effectiveness of the thermal barrier. In this study, YSZ coatings are deposited by plasma spraying using fused and crushed Y2O3-ZrO2 powder. Coating microstructure was modified by substrate temperature, which was varied from room temperature to 880 °C during deposition. The coating microstructure was examined from the fractured cross-section of the deposits to reveal changes in interla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The horizontal cracks were mainly resulted from the nonbonded interfaces within the coatings. According to our previous works [6,12,13], high substrate temperature redounded to the formation of a strong interlamella bonding with chemical effect in ceramic coatings. Consequently, the number of the horizontal cracks decreased with the increase of the substrate temperature from 50 o C to 240 o C. Generally, it is suggested that the pores in the coatings are mainly derived from gas trapping during deposition of melting particles.…”
Section: Resultsmentioning
confidence: 98%
“…The horizontal cracks were mainly resulted from the nonbonded interfaces within the coatings. According to our previous works [6,12,13], high substrate temperature redounded to the formation of a strong interlamella bonding with chemical effect in ceramic coatings. Consequently, the number of the horizontal cracks decreased with the increase of the substrate temperature from 50 o C to 240 o C. Generally, it is suggested that the pores in the coatings are mainly derived from gas trapping during deposition of melting particles.…”
Section: Resultsmentioning
confidence: 98%